2007
DOI: 10.1111/j.1365-2923.2007.02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Why people apply to medical school: implications for widening participation activities

Abstract: Our analysis provides evidence of important factors in career decision making for medicine which can be used to inform widening participation interventions in 3 areas, namely, those of school support, home support and raising aspirations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 18 publications
10
101
0
3
Order By: Relevance
“…Esse fato é relatado por ser muito significativo, sugerindo a importância de que mecanismos inconscientes estejam fortemente envolvidos na escolha, o que já foi bastante estudado [1][2][3][4] [1][2][3][4][5] , sendo o altruísmo o fator mais frequente, seguido de curiosidade científica, influência de terceiros, principalmente familiares, e motivação precoce, aqui chamada de fantasia ou sonho e na qual possivelmente estaria envolvido muito do inconsciente.…”
Section: A Opção Pela Medicinaunclassified
See 1 more Smart Citation
“…Esse fato é relatado por ser muito significativo, sugerindo a importância de que mecanismos inconscientes estejam fortemente envolvidos na escolha, o que já foi bastante estudado [1][2][3][4] [1][2][3][4][5] , sendo o altruísmo o fator mais frequente, seguido de curiosidade científica, influência de terceiros, principalmente familiares, e motivação precoce, aqui chamada de fantasia ou sonho e na qual possivelmente estaria envolvido muito do inconsciente.…”
Section: A Opção Pela Medicinaunclassified
“…A escolha da medicina como profissão, sem dúvida, resulta de vários fatores, alguns deles não conscientes e outros mais explícitos, e tem sido estudada no Brasil e no mundo [1][2][3][4] . Em estudo realizado na Universidade Federal de Minas Gerais (UFMG) em 2000, Ferreira et al 5 relataram que: Chamou ainda a atenção dos autores o fato de a inserção no mercado de trabalho não ter sido apontada como fator importante na escolha da profissão 5 .…”
Section: Introductionunclassified
“…A qualitative study in the UK among first-and second-year medical students to identify factors influencing students' motivation to apply to medical school showed that parent support and encouragement had a positive effect and lack of teacher support had a negative effect (McHarg et al 2007).…”
Section: Motivation As a Dependent Variablementioning
confidence: 99%
“…2 Such students have reportedly been deterred from application due to lack of teachers' understanding of what is "doctor material", suggesting that students are being insufficiently encouraged and guided toward medical school aspirations during the crucial period when their more affluent peers are being mentored toward such future careers. 3 Pipeline programmes exist in various places, but such programmes rely heavily on resource intensive visits by medical schools to a large number of student classrooms. Another way forward is greater education of teachers regarding the attributes medical schools seek in applicants, which might be achieved in part by circulating information in teachers' journals and empowering them to provide careers advice.…”
mentioning
confidence: 99%